2022
DOI: 10.1108/ecam-08-2021-0691
|View full text |Cite
|
Sign up to set email alerts
|

Critical factors of construction workers' career promotion: evidence from Guangzhou city

Abstract: PurposeThis study aims to build a framework of the influencing factors of construction workers' career promotion and identifies the critical determinants so as to propose suggestions for the government and enterprises to offer construction workers a path for career promotion.Design/methodology/approachIn line with the theory of human resources, such as Herzberg's two-factor theory, this study constructs a theoretical framework that affects the career promotion of construction workers. Using evidence from Guang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 113 publications
0
2
0
1
Order By: Relevance
“…Therefore, this study adopts strict random sampling to ensure that the sample can represent the real situation of construction workers in Guangzhou. Furthermore, Xie et al (2022) confirmed that the attitudes and behaviors of workers in a random sample of 50 programs were sufficiently diverse to yield valuable findings. Finally, 617 questionnaires were distributed and 489 questionnaires were returned, with the response rate of 79.25%.…”
Section: Sample Selection and Data Sourcesmentioning
confidence: 56%
“…Therefore, this study adopts strict random sampling to ensure that the sample can represent the real situation of construction workers in Guangzhou. Furthermore, Xie et al (2022) confirmed that the attitudes and behaviors of workers in a random sample of 50 programs were sufficiently diverse to yield valuable findings. Finally, 617 questionnaires were distributed and 489 questionnaires were returned, with the response rate of 79.25%.…”
Section: Sample Selection and Data Sourcesmentioning
confidence: 56%
“…W dotychczasowej literaturze dotyczącej rozwoju zawodowego wyróżnić można opracowania skoncentrowane na pracownikach zatrudnionych w poszczególnych działach organizacji (Bailey, 2015) lub branży, między innymi wysokich technologii (Berek, 2016) czy budowlanej (Xie i in., 2022). Stosunkowo niewiele badań podejmuje tematykę rozwoju zawodowego kobiet realizujących w organizacji funkcje zarządzania.…”
Section: Wstępunclassified
“…Zuckerman (1978) identified structural factors affecting access to career patterns in his study of medical officers in the United States. Another study by Xie et al (2022) in China found that age, tenure, job type, career development awareness, legal awareness, professional mentality, psychological training, and career development paths are important factors affecting employee career promotion. In government bureaucracies, career progression, typically in the form of promotions, is influenced by both formal and informal factors.…”
Section: Introductionmentioning
confidence: 99%